2011
DOI: 10.1021/bm2000023
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Diffusion of a Stiff Rod-Like Mutant Y21M fd-Virus

Abstract: We investigated the thermal diffusion phenomena of a rod-like mutant filamentous fd-Y21M virus in the isotropic phase, by means of an improved infrared thermal diffusion forced Rayleigh scattering (IR-TDFRS) set-up crucial for measurements of slowly diffusing systems.Since this is the first thermal diffusion study of a stiff anisotropic solute, we investigate the influence of the shape anisotropy on the thermal diffusion behavior. The influence of temperature, fd-Y21M concentration and ionic strength in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 61 publications
(132 reference statements)
3
44
0
Order By: Relevance
“…The solution changes from thermophobic at high temperatures, to thermophilic at low temperature, with the salt accumulating in the hot region in the latter case. The existence of temperature inversion effects in alkali halide aqueous solutions has been confirmed using state of the art thermal diffusion force Rayleigh scattering (TDRFS) [9,32,44] techniques as well as computer simulations [44]. This phenomenology can be consistently reproduced both experimentally and theoretically, and it is widely accepted.…”
Section: Introductionmentioning
confidence: 85%
“…The solution changes from thermophobic at high temperatures, to thermophilic at low temperature, with the salt accumulating in the hot region in the latter case. The existence of temperature inversion effects in alkali halide aqueous solutions has been confirmed using state of the art thermal diffusion force Rayleigh scattering (TDRFS) [9,32,44] techniques as well as computer simulations [44]. This phenomenology can be consistently reproduced both experimentally and theoretically, and it is widely accepted.…”
Section: Introductionmentioning
confidence: 85%
“…To measure the thermodiffusion, we used IR-TDFRS, a transient grating technique. 33,34 Two infra-red laser beams are crossed inside the sample and create a holographic grating that creates a temperature grating due to the inherent absorption of water in that range. 35 Thermodiffusion leads to migration of the particles in that temperature gradient and a superimposed concentration grating.…”
Section: B Thermal Diffusion Forced Rayleigh Scatteringmentioning
confidence: 99%
“…The thermodiffusive behavior of * j.olarte@imperial.ac.uk † mrubi@ub.edu ‡ f.bresme@imperial.ac.uk colloidal rods (fd viruses) was studied recently [13], and it has been shown that the heating of metallic nanorods in a polarized optical trap induces a thermal gradient around the rod and a torque that can be significant (∼10 2 pN nm) [14]. Theoretical and experimental studies of anisotropic particles under thermal gradients have uncovered fascinating behaviors that could open new routes to manipulate small colloids using thermal fields.…”
Section: Introductionmentioning
confidence: 99%